Implementasi Protokol MQTT (Message Queuing Telemetry Transport) Untuk Monitoring Infus Pasien Secara Terpusat - Sutikno Sutikno; Dahnial Syauqy; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Amount of patient and medical officers leads a new problems. One of them is about monitoring patient infusion fluid. Based on the case, a system is needed to monitor the patient's Infusion fluid when it is low, so that the officer is not late in replacing the intravenous fluids to the patient. To help overcome this problem, a system designed to monitor the patient's infusion centrally using MQTT (Message Queuing Telemetry Transport) delivery. The droplet reading is done by using a photodiode sensor by placing the sensor on the infusion chamber. Data processing on sensor node using NodeMCU and on server using PC / Laptop by utilizing websocket. The process of displaying data is done in realtime on the web interface. The test results on the three sensor nodes to detect the droplets yielded varying values ​​of 96%, 96%, and 94.6%. As for the test delay, obtained the average delay that occurs is 454.6 milli seconds.